If We Have Seen Further, It is By Standing on The Shoulders of Giants - Guillermo J. Ruiz-Argüelles; David Gomez-Almaguer; Guillermo J. Ruiz-Delgado; Andrés Gomez-; Iván Murrieta-Alvarez (Permanyer, 2021)
Dear Editor, In April 1960, Dr. Álvaro Gómez-Leal, a hematologist trained at the Instituto Nacional de Nutrición Salvador Zubirán (INCMNSZ), presented during the first meeting of the Agrupación Mexicana para el Estudio de la Hematología, A.C., data on a transplant of allogeneic stem cells in a patient with acute leukemia done in Monterrey,